Provisions related to the jurisprudential rule (additions to the text are not copies) a comparative jurisprudential study (Islamic Sciences Journal, 2024)
ABSTRACTPraise be to Allah, and prayers and peace be upon the Messenger of  Allah  and upon his family and companions. This research includes within its folds a comparative fundamentalist study on common fundamentalist jurisprudential rulings on a fundamentalist foundation. Is adding to the text not abrogated by the public? When they disagree that the addition to the text is abrogation, according to the majority, the fundamental rule adopted by them is that the addition to the text is not abrogation. In accordance with this rule, it included several provisions such as the obligation of intention in ablution, the obligation of reciting Surah Al-Fatihah in prayer, the obligation of a secure neck in expiation, and flogging with exile for men and women. Unmarried couples, and the ruling on witnessing with an oath, and all of these rulings need a comparative fundamentalist study to show the difference between the fundamentalists, and to explain to the reader the reason for the difference between fundamentalists and jurists on these issues, while mentioning the evidence of both groups. These rulings are essential in acts of worship, such as ablution, which is the condition for the validity of prayer. Likewise, reciting Surah Al-Fatihah in prayer, and prayer is one of the pillars of Islam, and it is subject to punishments such as flogging and banishment for unmarried men and women. Likewise, one of the important matters is judgment, such as judgment by witness with an oath. These are fundamentalist jurisprudential rulings. As for those who disagree with the majority of fundamentalists, namely the Hanafis - may  Allah  have mercy on them - they see implementation of the aforementioned fundamentalist rule. Above all, they do not impose what the majority of the aforementioned rulings have imposed; Because they consider these rulings to be an addition of a single report to the text of the Qur’an. Because they do not follow a single report and analogy based on the Qur’anic text, and I will explain later in the introduction in more detail, and from  Allah  is success.
Keywords: Provisions, related to, fundamental rule, addition, text, copy